Motor recovery after bilateral brachial plexus injury using motor irradiation: a case report. (22nd May 2019) - Oliveira, Laura Alice Santos de; Pedron, Carla Andressa; Andrade, Fernanda Guimarães de; Horsczaruk, Carlos Henrique Ramos; Martins, José Vicente Pereira
No abstract available